Tradisi Nyepeg Sampi Dalam Perspektif Hukum Dan Kebudayaan - Dio Kusumayuda, I Putu; Pasek Pramana, I Gede (Kertha Wicara : Journal Ilmu Hukum; Vol 10 No 1 (2020)DO - 10.24843/KW.2020.v10.i01.p04, 2020)
The purpose of this article is to determine and analyze the meaning of the Nyepeg Sampi tradition from a cultural perspective. As well as to examine the elements of acts against the law in the context of implementing the nyepeg sampi tradition. This article is classified as a type of normative legal research that uses an invited approach and a conceptual approach which also contains supporting data to assess legal materials which are the basis for analyzing legal issues being discussed. Based on the results of the analysis, it is known that the meaning of the nyepeg sampi tradition for peoples live in Asak-Karangasem Village is a ritual that aims to maintain the balance of nature. Given the meaning of the tradition of nyepeg sampi, therefore the nyepeg sampi tradition cannot be classified as a form of crime against animals as referred to in the provisions of Article 302 of the Criminal Code. Key Words: Nyepeg Sampi Tradition, Law, Culture.